2020
DOI: 10.1021/acs.jmedchem.9b02080
|View full text |Cite|
|
Sign up to set email alerts
|

Bicyclic α-Iminophosphonates as High Affinity Imidazoline I2 Receptor Ligands for Alzheimer’s Disease

Abstract: Imidazoline I 2 receptors (I 2-IR), widely distributed in the CNS and altered in patients that suffered from neurodegenerative disorders, are orphan from the structural point of view and new I 2-IR ligands are urgently required for improving their pharmacological characterization. We report the synthesis and 3D-QSAR studies of a new family of bicyclic -iminophosphonates endowed with relevant affinities for human brain I 2-IR. Acute treatment in mice with a selected compound significantly decreased the FADD pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 71 publications
3
28
0
Order By: Relevance
“…However, they did not investigate markers of neurodegeneration, glial activation or amyloid pathology, aside from some reductions in the levels of soluble APP-β fragment (Abás et al, 2020). Interestingly, the effects of BU224 treatment on reversing cognitive deficits observed in our study were not mediated by changes in amyloid deposition in the AD mouse model or in vitro.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, they did not investigate markers of neurodegeneration, glial activation or amyloid pathology, aside from some reductions in the levels of soluble APP-β fragment (Abás et al, 2020). Interestingly, the effects of BU224 treatment on reversing cognitive deficits observed in our study were not mediated by changes in amyloid deposition in the AD mouse model or in vitro.…”
Section: Discussionmentioning
confidence: 58%
“…Another recent study exploring the effect of chronic treatment with a new family of bicyclic α‐iminophosphonates with affinity for I 2 receptors reported improvements in memory deficits in 5XFAD mice using the novel object recognition test (Abás et al, 2020). However, they did not investigate markers of neurodegeneration, glial activation or amyloid pathology, aside from some reductions in the levels of soluble APP‐β fragment (Abás et al, 2020). Interestingly, the effects of BU224 treatment on reversing cognitive deficits observed in our study were not mediated by changes in amyloid deposition in the AD mouse model or in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably, the density of I 2 receptors was found to increase in AD patients (Garcia-Sevilla et al, 1998). Several lines of evidence provided by our group demonstrated that selective I 2 ligands protected against cognitive impairment and ameliorated AD pathological features related to amyloid precursor protein processing, tau hyperphosphorylation, neuroinflammation and oxidative stress processes, using well-established AD animal models (Ab as et al, 2017(Ab as et al, , 2020Griñ an-Ferré et al, 2019;.…”
Section: Introductionmentioning
confidence: 68%
“…Most notably, the density of I 2 receptors was found to increase in AD patients (Garcia‐Sevilla et al, 1998). Several lines of evidence provided by our group demonstrated that selective I 2 ligands protected against cognitive impairment and ameliorated AD pathological features related to amyloid precursor protein processing, tau hyperphosphorylation, neuroinflammation and oxidative stress processes, using well‐established AD animal models (Abás et al, 2017, 2020; Griñán‐Ferré et al, 2019; Vasilopoulou, Griñán‐Ferré, et al, 2020). Likewise, agmatine, the proposed endogenous ligand for I 2 receptors, prevented cognitive deficits in amyloid‐β 1–42 peptide‐injected mice and of note, its effect was augmented and attenuated by I 2 agonists and antagonists, respectively (Kotagale et al, 2020).…”
Section: Introductionmentioning
confidence: 91%